Penerapan Strategi Pembelajaran Berbasis Proyek dalam Pendidikan Islam untuk Meningkatkan Kesadaran Sosial Siswa - Muhammad Fadil; Saiyidinal Fajrus Salam; Gusmaneli Gusmaneli (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to explore the implementation of Project-Based Learning (PjBL) in Islamic education and its impact on students' social awareness. Project-Based Learning, which integrates active and collaborative learning, allows students to engage in projects that embody social values and Islamic teachings, such as empathy, justice, and social responsibility. Using a qualitative research method based on literature review, this study analyzes various literatures related to PjBL, Islamic education, and students' social character. The findings indicate that the implementation of PjBL can enhance students' social awareness by involving them in activities focusing on real-world social issues and linking them to Islamic principles. This method not only develops students' social skills but also strengthens their character in the context of Islamic values.